Analysis of the Implementation Package C Program at LPKA Kelas II Sungai Raya - Pratiwi, Riska Amanda; Imran, Imran; Utami, Patrisia Rahayu; Samodra, Y. Touvan Juni; Syamsuri, Syamsuri (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
Children in conflict with the law are entitled to receive education and rehabilitation while serving their sentences in the Juvenile Correctional Institution (LPKA). Education serves not only as an academic right but also as a means of moral and social rehabilitation. This study aims to analyze the implementation of the Package C Program for juvenile inmates at LPKA Class II Sungai Raya, Kubu Raya Regency, focusing on the aspects of planning, implementation, and outcomes. This research employed a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation involving LPKA officers, PKBM Khadijah educators, and juvenile participants. The findings indicate that the Package C Program was implemented through participatory planning based on learners’ needs, collaborative execution between LPKA and PKBM Khadijah, and continuous evaluation. The program positively impacted the cognitive, affective, psychomotor, and social development of the inmates. It not only functioned as an educational program but also as a medium for character formation and social reintegration. Conceptually, the implementation reflected non-formal education principles that are flexible, humanistic, and contextual, aligning with the objectives of the correctional system to build independent, responsible, and productive individuals. The study concludes that non-formal education within LPKA effectively supports the rehabilitation and empowerment of children in conflict with the law. Further research is recommended to strengthen experiential learning models and improve facilities and psychosocial support to enhance the sustainability of equality education programs in correctional institutions.